THE CONTENT OF NATURE FOUND IN WILLIAM SHAKESPEARE’S KING LEAR - Ali Fauzi (Program Studi PAI, Fakultas Tarbiyah, Institut Agama Islam Nahdlatul Ulama Tuban, 2017)
Drama is a literary work in which it reflects the activities of human beings and the surrounding life. It delineates life and human activity by means of presenting various actions of-and dialogues between-a group of characters. It also uses natural mimetic in form of symbolic nature of dramatic character and looks that nature becomes a part of subject matter which is quiet close to the action of men. The background of Shakespeare’s King Lear is the nature or the universe itself. Shakespeare uses the instrument of nature, the product of nature wholly and the hierarchy of the society combined with the medieval and old mythology to be the materials of his play. He uses the existence of nature to be interrelated with the parts, the naturalistic phenomena and with human beings and their life problems. The whole universe or nature is the cosmic system in which human beings form the system of social structure and live in harmony with other system where every element in the cosmos has its meaning only in relation to the other parts Therefore, it attracted Shakespeare so much to interpret the image of the cosmic system and its parts that the content of nature is richly found in the play. The content of nature consists of Cosmos including microcosm (a man, an animal-birds, a fox, an ape, an ass, wolves, a bull- a fiend and a sea monster, a Stock, a castle, a heath and hovel, clothes, music and medicine, a wheel) and macrocosm (a sun, a moon and other orbs, a storm, a rain, a thunder and lighting, an earth, an air, a fire and water, the insane, the death, the hell and the heaven).